In the name of the family : a novel - Dunant, Sarah (Random House, 2017)
Renowned for her bright and disciplined way with Renaissance Italy, New York Times best-selling novelist Dunant again visits the Borgias, to whom she recently paid court in Blood and Beauty. As Cesare ruthlessly seeks to unite all of Italy's city-states under Borgia control, Florence counters by sending one Niccolo Machiavelli to Rome as envoy and Lucrezia learns the family business of big-stakes political maneuvering.